Failing to Prepare Is Preparing to Fail: A Single-Blinded, Randomized Controlled Trial to Determine the Impact of a Preoperative Instructional Video on the Ability of Residents to Perform Laparoscopic Right Colectomy. Issue 1 (January 2016) - Crawshaw, Benjamin P.; Steele, Scott R.; Lee, Edward C.; Delaney, Conor P.; Mustain, W. Conan; Russ, Andrew J.; Shanmugan, Skandan; Champagne, Bradley J.
Abstract : BACKGROUND: Laparoscopic colorectal resection is an index case for advanced skills training, yet many residents struggle to reach proficiency by graduation. Current methods to reduce the learning curve for residents remain expensive, time consuming, and poorly validated. OBJECTIVE: The purpose of this study was to assess the impact of the addition of a preprocedural instructional video to improve the ability of a general surgery resident to perform laparoscopic right colectomy when compared with standard preparation. DESIGN: This was a single-blinded, randomized control study. SETTINGS: Four university-affiliated teaching hospitals were included in the study. PARTICIPANTS: General surgery residents in postgraduation years 2 through 5 participated. INTERVENTION: Residents were randomly assigned to preparation with a narrated instructional video versus standard preparation. MAIN OUTCOME MEASURES: Resident performance, scored by a previously validated global assessment scale, was measured. RESULTS: Fifty-four residents were included. Half (n = 27) were randomly assigned to view the training video and half (n = 27) to standard preparation. There were no differences between groups in terms of training level or previous operative experience or in patient demographics (all p > 0.05). Groups were similar in the percentage of the case completed by residents ( p = 0.39) and operative time ( p = 0.74). Residents in the video group scored significantly higher in total score (mean: 46.8 vs 42.3; p = 0.002), as well as subsections directly measuring laparoscopic skill (vascular control mean: 11.3 vs 9.7, p < 0.001; mobilization mean: 7.6 vs. 7.0, p = 0.03) and overall performance score (mean: 4.0 vs 3.1; p < 0.001). Statistical significance persisted across training levels. LIMITATIONS: There is potential for Hawthorne effect, and the study is underpowered at the individual postgraduate year level. CONCLUSIONS: The simple addition of a brief, narrated preprocedural video to general surgery resident case preparation significantly increased trainee ability to successfully perform a laparoscopic right colectomy. In an era of shortened hours and less exposure to cases, incorporating a brief but effective instructional video before surgery may improve the learning curve of trainees and ultimately improve safety.